1999
DOI: 10.1074/jbc.274.44.31217
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Enhancement of Quantal Catecholamine Secretion

Abstract: Prolonged exposure to hypoxia (10% O 2 ) enhanced quantal catecholamine release evoked from O 2 -sensing pheochromocytoma (PC12) cells, as monitored using single-cell amperometric recordings. The enhancement of exocytosis was apparent after 12 h of hypoxia and was maximal at 24 h. Elevated levels of secretion were due to the emergence of a Ca 2؉ influx pathway that persisted during complete blockade of known voltage-gated Ca 2؉ channels. Secretion triggered by this Ca 2؉ influx was severely reduced by known in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Further studies demonstrated that hypoxia increases cellular calcium influx, leading to elevated exocytosis (Bournaud et al, 2007; Carpenter et al, 2000; Mojet et al, 1997; Taylor et al, 1999). More recently, the involvement of NADPH oxidase and reactive oxygen species signalling in hypoxia-evoked catecholamine secretion has been established (Souvannakitti et al, 2010).…”
Section: Regulation Of Catecholamine Synthesis and Secretion By Hmentioning
confidence: 99%
“…Further studies demonstrated that hypoxia increases cellular calcium influx, leading to elevated exocytosis (Bournaud et al, 2007; Carpenter et al, 2000; Mojet et al, 1997; Taylor et al, 1999). More recently, the involvement of NADPH oxidase and reactive oxygen species signalling in hypoxia-evoked catecholamine secretion has been established (Souvannakitti et al, 2010).…”
Section: Regulation Of Catecholamine Synthesis and Secretion By Hmentioning
confidence: 99%
“…35 We have recently utilised this model to develop a clinically relevant bioassay for testing the efficacy of antioxidants in AD. 11,29,30 Exposure of cells to amyloid beta peptide residues 1 to 40 (AβP (1-40) ) causes a dramatic enhancement of Ca 2ϩ channel current in the clonal cell line PC12. 29, 30 We have confirmed that this event is linked to the generation of oxidative stressors as it is fully prevented by antioxidants.…”
Section: Pc12 Neuronal Cell Culture Experiments Indicative Of Admentioning
confidence: 99%
“…Indeed, we observed a strong clustering of upregulated energy-regulatory pathways associated with alternative energy production mechanisms (Figure 3C: GLYCOLYSIS_AND_GLUCONEOGENESIS , PPARAPATHWAY ), with a concomitant down-regulation of the mitochondrial oxidative phosphorylation functions ( ELECTRON_TRANSPORT , MOOTHA_VOXPHOS , MITOCHONDRIA_PATHWAY ). As oxidative and hypoxic events are often associated with the aging process and pathology [2], [7], [8], [11] we extracted PAGE pathways associated with these functions (Figure 3D). We noted that there was strong positive transcript population of age-related pathways ( AGED_MOUSE_CORTEX_UP , ALZHEIMERS_DISEASE_UP ), with a coherent negative population of converse pathways ( ALZHEIMERS_DISEASE_DN , AGEING_BRAIN_DN ).…”
Section: Resultsmentioning
confidence: 99%